The Fear of COVID-19 Raises the Level of Depression, Anxiety and Stress through the Mediating Role of Intolerance of Uncertainty - Kardaş, Ferhat (Studia Psychologica, 2021)
The COVID-19 pandemic results in various psycho-social effects, including adverse effects on mental health on the general population. Many studies across different countries showed a significant increase in symptoms of fear, depression, anxiety and stress compared to the situation before the COVID-19 outbreak. Thus, it has gained more importance to examine the relationship between fear of the disease with mental health problems. This study aims to investigate the mediating role of intolerance to uncertainty on the relationship between COVID-19 fear and depression, anxiety and stress. The sample of the study consisted of 679 individuals, including 467 (68.8 %) and 212 males (31.2 %). Data were collected through an online survey using The Fear of COVID-19 Scale, Intolerance to Uncertainty Scale and Depression, Anxiety and Stress (Das-21) Scale. Correlation analysis, structural equation modeling and process analysis were used for data analysis. A significant positive relationship was reached between COVID-19 fear and intolerance to uncertainty, depression, anxiety, and stress. All variables were found as differing significantly concerning gender. Intolerance to uncertainty was found as fully mediating the relationship between fear of COVID-19 and depression, anxiety and stress. The findings obtained in this study were discussed and various suggestions were presented.